The Application of Augmented Reality in Furniture Purchasing and Evaluation Based on the System Usability Scale (SUS) - Muhammad Fajrian Noor; Sofyar Sofyar; Dwipayana Ismulya; M. Utiya Raihan; Aqil Rahmatullah; M. Renald Abdi (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2025)
The furniture industry is undergoing a significant digital transformation, reshaping how consumers interact and make purchasing decisions. Augmented Reality (AR) technology enables users to visualise furniture products in their actual physical spaces before making a purchase, offering a more interactive, realistic, and personalised shopping experience. This study aims to evaluate the effectiveness of AR technology in supporting online furniture purchasing by applying the ADDIE development model and assessing usability through the System Usability Scale (SUS) method. A total of 35 respondents, representing millennial and Gen Z users aged between 18 untill 35, participated in testing an AR-based furniture shopping application. The research findings indicate that the application achieved an average SUS score of 81.5, which falls into the "Excellent" usability category, signifying a high level of user satisfaction and acceptance. The results also reveal that AR improves consumer confidence in product selection by allowing realistic visualisation of furniture items in users' own environments. Therefore, this study concludes that integrating AR technology in digital commerce not only enhances user experience but also provides an effective marketing strategy for furniture businesses to strengthen customer engagement, trust, and purchase decisions in the digital era.